2017
DOI: 10.1016/j.cemconres.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

NMR observation of water transfer between a cement paste and a porous medium

Abstract: We show that it is possible to follow the liquid transfer between a cement paste and a porous medium in contact with it, by analyzing the evolution of the distribution of 1 H NMR relaxation times. This in particular makes it possible to see that whatever the initial water fraction in the paste, a porous medium with sufficiently small pores can rapidly extract a significant amount of water from this paste. Afterwards, during the hydration process, the cement paste progressively gets water back from this porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…This could be attributed to the development of a denser microstructure upon hydration. On the other hand, the increase in the w/b ratio increased the peak intensities, which is in line with Fourmentin et al 26 The additional peak (Peak 2), observed in the 10-200 ms range, is attributed to the free water in larger capillary pores. As expected, its intensity is significantly larger in the pure Portland cement with SAP than that without SAP due to the water absorbed by SAP.…”
Section: Absorption/desorption Kinetics Of Sap In Pure Portland Cement Pastesupporting
confidence: 89%
See 1 more Smart Citation
“…This could be attributed to the development of a denser microstructure upon hydration. On the other hand, the increase in the w/b ratio increased the peak intensities, which is in line with Fourmentin et al 26 The additional peak (Peak 2), observed in the 10-200 ms range, is attributed to the free water in larger capillary pores. As expected, its intensity is significantly larger in the pure Portland cement with SAP than that without SAP due to the water absorbed by SAP.…”
Section: Absorption/desorption Kinetics Of Sap In Pure Portland Cement Pastesupporting
confidence: 89%
“…NMR is a versatile non-destructive technique that allows gathering quantitative and qualitative information on cement hydration, its pore structure and the state of water in porous materials. This technique, extensively described in other studies, 23,24,25,26 makes it possible to easily distinguish between the free water in the cement matrix and the water in SAP by studying the evolution of H-NMR signals associated with changes in the matrix pore structure. 24,25,27,28 Furthermore, the strong changes in the NMR relaxation time that occur as a result of the development of the matrix pore structure provide insight into the transfer of water into SAP and from SAP back into concrete.…”
mentioning
confidence: 99%
“…Moisture profiles of porous materials during heating could be studied and conclusions could be drawn on how the water escaped the sample as a function of time 32 , 33 . The profiles can be used to study drying or saturation of a mortar sample 34 , 35 , the water release from a cement paste to a porous material 36 or for autogenous healing 37 . Only a few studies utilizing NMR relaxometry for water release by SAPs towards the cementitious matrix have been done.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is supported by MRI observations of the transfers between two solid porous media in contact [14][15]. However, it was already remarked that the water contained of a cement paste in contact with an initially dry bed packing (with larger pores) can be extracted by capillary effects so as to finally saturate the bead packing [16]. These observations were carried out by NMR (Nuclear Magnetic Resonance) on bead packing samples surrounded by paste.…”
Section: Introductionmentioning
confidence: 77%